Systemic Response to Infection Induces Long-Term Cognitive Decline: Neuroinflammation and Oxidative Stress as Therapeutical Targets - Reis, Patricia Alves; Castro-Faria-Neto, Hugo Caire (Frontiers in Neuroscience, 2022)
In response to pathogens or damage signs, the immune system is activated in order to eliminate the noxious stimuli. The inflammatory response to infectious diseases induces systemic events, including cytokine storm phenomenon, vascular dysfunction, and coagulopathy, that can lead to multiple-organ dysfunction. The central nervous system (CNS) is one of the major organs affected, and symptoms such as sickness behavior (depression and fever, among others), or even delirium, can be observed due to activation of endothelial and glial cells, leading to neuroinflammation. Several reports have been shown that, due to CNS alterations caused by neuroinflammation, some sequels can be developed in special cognitive decline. There is still no any treatment to avoid cognitive impairment, especially those developed due to systemic infectious diseases, but preclinical and clinical trials have pointed out controlling neuroinflammatory events to avoid the development of this sequel. In this minireview, we point to the possible mechanisms that triggers long-term cognitive decline, proposing the acute neuroinflammatory events as a potential therapeutical target to treat this sequel that has been associated to several infectious diseases, such as malaria, sepsis, and, more recently, the new SARS-Cov2 infection.